2021
DOI: 10.1186/s13019-021-01677-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter mitral valve replacement for degenerated mitral valve bioprostheses, failure of mitral valvuloplasty and native valve with severe mitral annulus calcification: a systematic review and meta-analysis

Abstract: Background Although transcatheter technology has achieved some success in the field of mitral valves, the feasibility of applying it to patients with degenerated mitral valve bioprostheses (valve-in-valve, ViV), failure of mitral valvuloplasty (valve-in-ring, ViR) and serious mitral annulus calcification (vale-in-MAC, ViMAC) has not been effectively evaluated. Methods By searching published literature before December 5, 2020 in four databases, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…cerebrovascular, bleeding/vascular, or repeat surgery. Other larger international cohort studies reported 30-day mortality reaching up to 8% with other adverse events also more frequently occurring when describing outcomes of early experiences [12]. These promising clinical results coming from this first experience in Poland are probably attributable to the later adoption of this technique in Poland and thereby avoidance of most of the issues characteristic of early stages of ViV-TMVI (e.g.…”
Section: Discussionmentioning
confidence: 65%
“…cerebrovascular, bleeding/vascular, or repeat surgery. Other larger international cohort studies reported 30-day mortality reaching up to 8% with other adverse events also more frequently occurring when describing outcomes of early experiences [12]. These promising clinical results coming from this first experience in Poland are probably attributable to the later adoption of this technique in Poland and thereby avoidance of most of the issues characteristic of early stages of ViV-TMVI (e.g.…”
Section: Discussionmentioning
confidence: 65%
“…Guerrero et al 8 performed transcatheter MV replacement for patients with severe MAC who were not surgical candidates, they found cardiac‐CT based score provided a systematic method to grade MAC severity which may assist in predicting valve embolization/migration. A meta‐analysis showed that the feasibility of transcatheter technology in serious MAC needed to be further explored and improved 42 . The experience in this aspect is still limited and general recommendations cannot yet be made 16 .…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis showed that the feasibility of transcatheter technology in serious MAC needed to be further explored and improved. 42 The experience in this aspect is still limited and general recommendations cannot yet be made. 16 But what is certain is that imaging is critical to the success of these surgical and transcatheter therapies.…”
Section: Discussionmentioning
confidence: 99%
“…[25,26] In the era of micro-invasive procedures, transcatheter valve repair or replacement should be definitely be considered an alternative to traditional or minimally invasive cardiac surgery in fragile and high-risk patients such as octogenarians. [27] However, it is well-known that micro-invasive procedures have strict parameters of selection, particularly regarding the anatomy of the MV or TV; therefore, a not negligible proportion of patients are excluded from the benefits of these options. Moreover, wh-en looking at micro-invasive options for MV replacement, suboptimal outcomes in terms of in-hospital mortality and weaknesses of the procedure, such as iatrogenic left ventricular outflow tract obstruction and MV stenosis, are still reported and represent a restraint in the broader adoption of these techniques.…”
Section: Discussionmentioning
confidence: 99%